Carbonic acid monoethyl ester as a pure solid and its conformational isomerism in the gas-phase. Issue 36 (21st April 2017) - Bernard, Jürgen; Köck, Eva-Maria; Huber, Roland G.; Liedl, Klaus R.; Call, Ludwig; Schlögl, Robert; Grothe, Hinrich; Loerting, Thomas
Abstract : The ethyl hemiester of carbonic acid is prepared as a pure solid and sublimed to the gas phase, in spite of claims of its instability. FT-IR spectroscopy combined with ab initio calculations reveals a 5 : 1 ratio of the two most stable conformers. Abstract : The monoesters of carbonic acid are deemed to be unstable and decompose to alcohol and carbon dioxide. In spite of this, we here report the isolation of the elusive carbonic acid monoethyl ester (CAEE) as a pure solid from ethanolic solutions of potassium bicarbonate. The hemiester is surprisingly stable in acidic solution and does not experience hydrolysis to carbonic acid. Furthermore, it is also stable in the gas phase, which we demonstrate by subliming the hemiester without decomposition. This could not be achieved in the past for any hemiester of carbonic acid. In the gas phase the hemiester experiences conformational isomerism at 210 K. Interestingly, the thermodynamically favored conformation is only reached for the torsional movement of the terminal ethyl group, but not the terminal hydrogen atom on the millisecond time scale. Accordingly, IR spectra of the gas phase trapped in an argon matrix are best explained on the basis of a 5 : 1 mixture of monomeric conformers. Our findings necessitate reevaluation of claims of the formation of a carbonic acid polymorph in methanolic solution, which is the subject of a forthcoming publication.